Common bacterial blight - Saettler, A.W. (International Center for Tropical Agriculture, 1989)
Common bacterial blight (Xanthomonas campestris pv. phaseoli) is the major bacterial disease of beans. The organism is present in numerous bean production regions of the world. High temp. and RH are favorable conditions for the development of the disease. The infection by the bacteria produces water-soaked spots on the leaves, stems, pods, and seeds. The disease can be controlled by cultural practices such as the use of disease-free seed, proper crop rotation with resistant crops, the use of various chemical products in seed treatment or as a foliage protectant before the infection becomes severe, the use of resistant var., and integrated control. The symptoms and damage caused by the disease are illustrated in color. (CIAT)